Water-based wood-like polyurethane and preparation method thereof

By combining bamboo nanocellulose with water-based polyurethane to form hydrogen bonds and covalent crosslinking networks, the problem of insufficient mechanical properties and water resistance of existing water-based polyurethane imitation wood materials after flame retardant modification is solved, and the good mechanical properties, water resistance and flame retardant properties of the material are achieved.

CN119661808APending Publication Date: 2025-03-21ZHEJIANG LISHUI BOSHIDA POLYMER MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411949836.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-07-17
Filing Date
2024-12-27
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

After the flame retardant modification of existing water-based polyurethane imitation wood materials, there are insufficient mechanical properties and water resistance, which limits its further application.

Method used

By preparing bamboo nanocellulose and combining it with aqueous polyurethane, a hydrogen bond and covalent crosslinking network is formed to improve the mechanical properties and water resistance of the material while enhancing its flame retardant properties.

Benefits of technology

It has achieved good mechanical properties and water resistance of water-based imitation wood-type polyurethane materials, and has certain flame retardant properties, and is suitable for high-end export furniture and interior decoration projects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119661808A_ABST
    Figure CN119661808A_ABST
Patent Text Reader

Abstract

The invention discloses water-based wood-like polyurethane and a preparation method thereof.The stock solution of the water-based wood-like polyurethane comprises a phase A with polyoxytetramethylene glycol as a main component and a phase B composed of 4, 4 '-methylene bis (phenyl isocyanate) and bamboo nanocellulose suspension liquid, the two phases are stirred and foamed, and the water-based wood-like polyurethane is obtained. The waterborne polyurethane wood-like material can be obtained. The waterborne polyurethane wood-like material prepared by the preparation method disclosed by the invention has a certain water resistance and flame-retardant effect, and also has good mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, in particular to a water-based wood-like polyurethane and a preparation method thereof. Background Art

[0002] With the rapid development of society and economy, people's exploitation of natural resources has also increased. However, due to excessive exploitation, it has caused serious harm to the earth's environment. Among them, due to the indiscriminate logging and over-exploitation of forest resources, the forest ecosystem has been severely damaged, and the vegetation has seriously degraded, which has aggravated soil erosion and land desertification, seriously damaging the ecological balance and people's living environment. Therefore, people have planted trees and reduced the exploitation of forest resources to alleviate soil erosion and soil desertification and improve the environment. This change has led to a significant decline in the supply capacity of wood resources, making the contradiction between supply and demand of wood gradually prominent. In response to this problem, people began to study different types of engineered wood, artificial wood and imitation wood materials to alleviate the shortage of wood resources.

[0003] Polyurethane rigid foamed wood-like materials have become a new field of research and development in my country due to their excellent physical properties and processing properties, and have been used in high-end export furniture and interior decoration projects. Waterborne polyurethane wood-like materials are popular because of their stable structure, non-deformation, light weight, good processing performance, long life, and green and pollution-free characteristics. However, waterborne polyurethane is a flammable material with a fast burning speed and rapid flame propagation. In addition, high-temperature molten droplets will be produced during the combustion process, posing a hidden danger of causing fire. Therefore, flame-retardant modification of waterborne polyurethane to improve its flame-retardant properties is an important development direction for the functionalization of waterborne polyurethane materials.

[0004] At present, most studies have shown that the flame retardant properties of waterborne polyurethane can be significantly improved by adding flame retardants, reducing the heat release rate and increasing the residual carbon rate, thereby slowing down the spread of fire and reducing casualties and property losses when a fire occurs. However, the mechanical properties of most waterborne polyurethane wood-like materials will be more or less reduced due to the addition of flame retardants, and polyurethane wood-like materials generally have defects such as poor water resistance, which limits their further application. In order to improve the performance of polyurethane, the use of nanomaterials is one of the most widely used and effective methods, but most studies are inorganic nanomaterials, some of which have defects such as high prices. Cellulose nanomaterials, as an emerging biomass nanomaterial, have certain development prospects in improving the performance of polyurethane. Bamboo is a short-lived, sustainable, environmentally friendly and multifunctional grass plant. Bamboo nanocellulose obtained by certain treatment can replace expensive materials as an environmentally friendly material.

[0005] Therefore, in view of the above problems, the present invention provides a water-based wood-like polyurethane and a preparation method thereof. Summary of the invention

[0006] In view of the above problems in the prior art, the present invention provides a water-based wood-like polyurethane and a preparation method thereof, with the aim of developing a water-based wood-like polyurethane having a flame retardant effect and good mechanical properties.

[0007] To achieve the above object, the present invention adopts the following technical solutions: A water-based wood-like polyurethane, characterized in that the preparation method of the water-based wood-like polyurethane comprises the following steps: (1) Preparation of bamboo nanocellulose: S1: Put bamboo powder and acetic acid solution into a reaction tank. Place the reaction tank of the mixed solution in an electric rotary pot, heat at 120-180°C for 45-80min, take it out, cool it at 24-28°C for 4.5-8h, and finally separate the prehydrolyzed bamboo powder from the prehydrolyzate with a Buchner funnel, dry it at 35-50°C, and obtain a prehydrolyzed bamboo powder sample.

[0008] S2: FeCl3·6H2O, tetrabutylammonium acetate and polyphosphoric acid were placed in a three-necked flask and reacted in a water bath at 60-80°C for 1.5-4h to form a uniform solution A. Subsequently, the pre-hydrolyzed bamboo powder sample prepared in S1 was added, reacted at a speed of 200-350r / min for 5-8h, deionized water was added to dilute the mixture, centrifuged at a speed of 7500-9000r / min for 5-16min, and the above operation was repeated 2-3 times to obtain a bamboo nanocellulose suspension.

[0009] (2) Preparation of water-based wood-like polyurethane stock solution: It is composed of two components A and B. Polyoxytetramethylene glycol, dihydroxyethyl dodecylamine, polysilane, dibutyltin dilaurate and water are placed in a container at 25-40°C and stirred to obtain component A. Component B is 4,4'-methylenebis(phenyl isocyanate) and the bamboo nanocellulose suspension obtained in step (1) are placed in a container and stirred for 25-45 minutes to obtain a uniform mixture.

[0010] In one implementation method, in step (1), the ratio of bamboo powder (g) to acetic acid solution (mL) is 1:(8-15), and the concentration of the acetic acid solution is 1.5 mol / L.

[0011] In one implementation method, the molar ratio of FeCl3·6H2O, polyphosphoric acid and tetrabutylammonium acetate in the solution in step (1) is (0.1-0.5):(1-5):1.

[0012] In one implementation method, in step (1), the ratio of the hydrolyzed bamboo powder sample (g) to solution A (mL) is 1:(5-12), and the volume ratio of solution A to deionized water is 1:(1.5-2).

[0013] In one implementation method, the mass ratio of polyoxytetramethylene glycol, dihydroxyethyl dodecylamine, polysilane, dibutyltin dilaurate and water in phase A in step (2) is (45-80): (8-20): (0.3-1.0): 1: (0.2-0.8).

[0014] In one implementation method, the mass ratio of 4,4'-methylenebis(phenyl isocyanate) to the bamboo nanocellulose suspension in phase B in step (2) is 1:(0.01-0.05).

[0015] In one implementation method, the preparation method of the water-based wood-like polyurethane material is to stir group A and group B with a mass ratio of 1: (1-1.5) at a speed of 550-750 r / min for 30-75 seconds, and then immediately introduce them into a mold for foaming for 1-2 hours to obtain a water-based polyurethane wood-like material, and the foaming temperature is 20-28°C.

[0016] Compared with the prior art, the present invention has the following beneficial effects: 1. After further processing of bamboo powder by the present invention, bamboo nano cellulose with good dispersibility is obtained, so that it is evenly filled on waterborne polyurethane, and the finally prepared waterborne polyurethane imitation wood material has a more uniform porous structure. The bamboo nano cellulose and waterborne polyurethane generate hydrogen bonds to form a tight covalent cross-linked network, forming a stable and rigid pore skeleton, so that the wood-like material has a higher compressive strength-to-weight ratio, bending strength-to-weight ratio and tensile strength-to-weight ratio at the same density. Therefore, the wood-like material prepared by the waterborne imitation wood type polyurethane stock solution of the present invention has good mechanical properties.

[0017] 2. The waterborne polyurethane wood-like material obtained by foaming of the present invention has certain water resistance, and its contact angle can reach 96.75°, and it has certain flame retardant performance, and its limiting oxygen index can reach 24.1%, and the residual carbon rate can reach 33.1%. In addition, the bamboo nanocellulose added in the waterborne polyurethane of the present invention is obtained by processing bamboo powder, which has the advantages of low cost and environmental protection.

[0018] Other advantages, objectives and features of the present invention will be reflected in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 is the water contact angle of Example 1.

[0020] Figure 2 This is a SEM schematic diagram of Example 1. DETAILED DESCRIPTION

[0021] The present invention is specifically described below by way of examples, which are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. It should be understood that after reading the contents of the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.

[0022] Example 1 The preparation steps of the water-based wood-like polyurethane material are as follows: (1) Preparation of bamboo nanocellulose: S1: Put 60g of bamboo powder and 600mL of acetic acid solution into a reaction tank. Place the reaction tank of the mixed solution in an electric rotary pot, heat it at 160°C for 60min, take it out, cool it at 26°C for 6h, and finally separate the prehydrolyzed bamboo powder from the prehydrolyzate with a Buchner funnel, dry it at 40°C, and obtain a prehydrolyzed bamboo powder sample.

[0023] S2: 2.7 g of FeCl3·6H2O, 30.5 g of tetrabutylammonium acetate and 67.6 mL of polyphosphoric acid were placed in a three-necked flask and reacted in a water bath at 65°C for 2 h to form a uniform solution. Subsequently, 6 g of the hydrolyzed bamboo powder sample prepared in S1 was added, reacted at a speed of 300 r / min for 6 h, 110 mL of deionized water was added to dilute the above mixture, and centrifuged at a speed of 8000 r / min for 10 min. The above operation was repeated 3 times to obtain a bamboo nanocellulose suspension.

[0024] (2) Preparation of water-based wood-like polyurethane stock solution: It consists of two components, A and B. 100 g of polyoxytetramethylene glycol, 20 g of dihydroxyethyl dodecylamine, 0.8 g of polysilane, 2 g of dibutyltin dilaurate and 0.6 g of water were placed in a container at 30°C and stirred to obtain component A. Component B was 165 g of 4,4'-methylenebis(phenyl isocyanate) and 3.3 g of bamboo nanocellulose suspension placed in a container and stirred for 30 min to obtain a uniform mixture.

[0025] (3) Water-based wood-like polyurethane material: 80 g of phase A and 96 g of phase B were stirred at 600 r / min for 60 s, and then immediately introduced into a mold and foamed at 25°C for 1.5 h to obtain a water-based polyurethane wood-like material.

[0026] Example 2 The preparation steps of the water-based wood-like polyurethane material are as follows: (1) Preparation of bamboo nanocellulose: S1: 80g of bamboo powder and 360mL of acetic acid solution were placed in a reaction tank. The reaction tank of the mixed solution was placed in an electric rotary pot, heated at 120°C for 45min, taken out, and cooled at 24°C for 4.5h. Finally, the prehydrolyzed bamboo powder was separated from the prehydrolyzate using a Buchner funnel, and dried at 35°C to obtain a prehydrolyzed bamboo powder sample.

[0027] S2: 5.4 g of FeCl3·6H2O, 61 g of tetrabutylammonium acetate and 135 mL of polyphosphoric acid were placed in a three-necked flask and reacted in a water bath at 60°C for 1.5 h to form a uniform solution. Subsequently, 13 g of the hydrolyzed bamboo powder sample prepared in S1 was added, reacted at a speed of 200 r / min for 5 h, 205 mL of deionized water was added to dilute the above mixture, and centrifuged at a speed of 7500 r / min for 5 min. The above operation was repeated twice to obtain a bamboo nanocellulose suspension.

[0028] (2) Preparation of water-based wood-like polyurethane stock solution: It consists of two components, A and B. 85 g of polyoxytetramethylene glycol, 16 g of dihydroxyethyl dodecylamine, 0.6 g of polysilane, 1.6 g of dibutyltin dilaurate and 0.5 g of water were placed in a container at 25°C and stirred to obtain component A. Component B was 130 g of 4,4'-methylenebis(phenyl isocyanate) and 1.3 g of bamboo nanocellulose suspension placed in a container and stirred for 25 min to obtain a uniform mixture.

[0029] (3) Water-based wood-like polyurethane material: 80 g of each phase A and phase B were stirred at a speed of 550 r / min for 45 seconds, and then immediately introduced into a mold and foamed at 22° C. for 1 hour to obtain a water-based polyurethane wood-like material.

[0030] Example 3 The preparation steps of the water-based wood-like polyurethane material are as follows: (1) Preparation of bamboo nanocellulose: S1: 45g of bamboo powder and 670mL of acetic acid solution were placed in a reaction tank. The reaction tank of the mixed solution was placed in an electric rotary pot, heated at 180°C for 80min, taken out, and cooled at 28°C for 8h. Finally, the prehydrolyzed bamboo powder was separated from the prehydrolyzate using a Buchner funnel, and dried at 45°C to obtain a prehydrolyzed bamboo powder sample.

[0031] S2: 1 g of FeCl3·6H2O, 10.2 g of tetrabutylammonium acetate and 23 mL of polyphosphoric acid were placed in a three-necked flask and reacted in a water bath at 80°C for 4 h to form a uniform solution. Subsequently, 2 g of the hydrolyzed bamboo powder sample prepared in S1 was added, reacted at a speed of 350 r / min for 8 h, 45 mL of deionized water was added to dilute the above mixture, and centrifuged at a speed of 9000 r / min for 16 min. The above operation was repeated 3 times to obtain a bamboo nanocellulose suspension.

[0032] (2) Preparation of water-based wood-like polyurethane stock solution: It consists of two components, A and B. 110 g of polyoxytetramethylene glycol, 20 g of dihydroxyethyl dodecylamine, 0.8 g of polysilane, 1.5 g of dibutyltin dilaurate and 0.5 g of water were placed in a container at 40°C and stirred to obtain component A. Component B was 130 g of 4,4'-methylenebis(phenyl isocyanate) and 3.9 g of bamboo nanocellulose suspension placed in a container and stirred for 45 min to obtain a uniform mixture.

[0033] (3) Water-based wood-like polyurethane material: 100 g of phase A and 120 g of phase B were stirred at 750 r / min for 75 s, and then immediately introduced into a mold and foamed at 28° C. for 2 h to obtain a water-based polyurethane wood-like material.

[0034] Comparative Example 1 The preparation steps of the common water-based wood-like polyurethane material are as follows: (1) Preparation of water-based wood-like polyurethane stock solution: It consists of two components, A and B. 100 g of polyoxytetramethylene glycol, 20 g of dihydroxyethyl dodecylamine, 0.8 g of polysilane, 2 g of dibutyltin dilaurate and 0.6 g of water are placed in a container at 30°C and stirred to obtain component A. Component B is 165 g of 4,4'-methylenebis(phenyl isocyanate) and 3.3 g of bamboo nanocellulose suspension placed in a container and stirred for 30 min to obtain a uniform mixture.

[0035] (2) Water-based wood-like polyurethane material: 80 g of phase A and 96 g of phase B were stirred at 600 r / min for 60 s, and then immediately introduced into a mold and foamed at 25° C. for 1.5 h to obtain a water-based polyurethane wood-like material.

[0036] Comparative Example 2 The preparation steps of the water-based wood-like material are as follows: (1) Preparation of bamboo nanocellulose: S1: 60g of bamboo powder and 600mL of acetic acid solution were placed in a reaction tank. The reaction tank of the mixed solution was placed in an electric rotary pot, heated at 160°C for 60min, taken out, and cooled at 24°C for 6h. Finally, the prehydrolyzed bamboo powder was separated from the prehydrolyzate using a Buchner funnel, and dried at 35°C to obtain a prehydrolyzed bamboo powder sample.

[0037] S2: 2.7 g of FeCl3·6H2O, 30.5 g of tetrabutylammonium acetate and 46.0 mL of formic acid were placed in a three-necked flask and reacted in a water bath at 65°C for 2 h to form a uniform solution. Subsequently, 4.6 g of hydrolyzed bamboo powder sample was added and reacted at a speed of 300 r / min for 6 h. 85 mL of deionized water was added to dilute the above mixture, and centrifuged at a speed of 8000 r / min for 10 min. The above operation was repeated 3 times to obtain a bamboo nanocellulose suspension.

[0038] (2) Preparation of water-based wood-like polyurethane stock solution: It consists of two components A and B. 100 g of polyoxytetramethylene glycol, 20 g of dihydroxyethyl dodecylamine, 0.8 g of polysilane, 2 g of dibutyltin dilaurate and 0.6 g of water are placed in a container at 30°C and stirred to obtain component A. Component B is 165 g of 4,4'-methylenebis(phenyl isocyanate) and 3.3 g of bamboo nanocellulose suspension placed in a container and stirred for 30 min to obtain a uniform mixture.

[0039] Water-based wood-like polyurethane material: 80 g of phase A and 96 g of phase B were stirred at a speed of 600 r / min for 60 seconds, and then immediately introduced into a mold and foamed at 25° C. for 1.5 hours to obtain a water-based polyurethane wood-like material.

[0040] Comparative Example 3 The preparation steps of the flame retardant waterborne polyurethane wood-like material are as follows: (1) Preparation of water-based wood-like polyurethane stock solution: It consists of two components, A and B. 100 g of polyoxytetramethylene glycol, 20 g of expandable graphite / methyl dimethyl phosphate (mass ratio of 0.8:1), 0.8 g of polysilane, 2 g of dibutyltin dilaurate and 0.6 g of water were placed in a container at 30°C and stirred to obtain component A. Component B, which is 165 g of 4,4'-methylenebis(phenyl isocyanate) and 3.3 g of bamboo nanocellulose suspension, was placed in a container and stirred for 30 min to obtain a uniform mixture.

[0041] (2) Water-based wood-like polyurethane material: 80 g of phase A and 96 g of phase B were stirred at 600 r / min for 60 s, and then immediately introduced into a mold and foamed at 25°C for 1.5 h to obtain a water-based polyurethane wood-like material.

[0042] Experimental methods Implementations 1 to 3 and Comparative Examples 1 to 3 were tested, wherein the density, mechanical properties, contact angle, scanning electron microscopy, LOI and combustion behavior test methods were as follows: Mechanical properties: Use TX-8001 universal testing machine to test mechanical properties. According to GB / T6343-2009 (Determination of apparent density of foam plastics and rubber), prepare 100mm×100mm×50mm samples, use vernier calipers to accurately measure their length, width and height, take three points of each dimension, take the middle value, accurate to 0.01; use electronic balance to weigh its mass, accurate to 0.0001g, prepare 5 samples in each group, and calculate its average apparent density.

[0043] Limiting Oxygen Index (LOI) test: The minimum oxygen percentage required to burn a sample in an O2-N2 atmosphere is tested in accordance with GB / T2406.2-2009. The sample size is 100mm×6.5mm×3mm. Each sample is tested 5 times and the average value is taken.

[0044] The combustion behavior of waterborne polyurethane was tested using a FTT0007 cone calorimeter. The samples were cut into 15 cm × 15 cm blocks and the implementation standard was ISO 5669.

[0045] Water contact angle test: Use a contact angle tester to characterize the wettability of the polyurethane coating surface. Use a micro syringe to carefully drop about 2.5μL of distilled water on the sample surface and record and photograph the liquid morphology.

[0046] Scanning electron microscopy (SEM) analysis: Field emission scanning electron microscopy was used for scanning tests, and all samples were cut into thin slices for testing.

[0047] The test results are shown in the attached manual. Figure 1~2 , Tables 1~3.

[0048] Tables 1 and 2 are respectively the mechanical data and strength-to-weight ratio of the embodiment and the comparative example. As shown in Table 1, the apparent density of the embodiment and the comparative example is between 0.45 and 0.6, which is similar to the density of wood. The mechanical properties of comparative example 3 are worse than those of comparative example 1, indicating that the addition of flame retardant will have a certain adverse effect on the mechanical properties of polyurethane. In addition, the mechanical properties of comparative example 2 are similar to those of embodiments 1 to 3, and are better than comparative example 1. As shown in Table 2, the compressive strength-to-weight ratio of embodiment 1 is 27% higher than that of comparative example 1, the tensile strength-to-weight ratio of embodiment 1 is 50.1% higher than that of comparative example 1, and the bending strength-to-weight ratio of embodiment 1 is 47.67% higher than that of comparative example 1, further illustrating that bamboo nano-cellulose can improve the mechanical properties of polyurethane. Therefore, the wood-like material prepared by the water-based wood-like polyurethane of the present invention has good mechanical properties.

[0049] Table 1 Mechanical properties data of examples and comparative examples sample Apparent density g / cm3 Compressive strength MPa Tensile strength MPa Bending strength MPa Example 1 0.51 12.9 11.4 25.1 Example 2 0.47 10.6 9.2 23.9 Example 3 0.48 11.8 10.0 23.7 Comparative Example 1 0.45 8.9 6.7 15.0 Comparative Example 2 0.50 11.5 10.5 24.1 Comparative Example 3 0.46 7.1 5.9 13.9 Table 2 Strength-to-weight ratio of examples and comparative examples sample Compression strength to weight ratio Tensile strength to weight ratio Bending strength to weight ratio Example 1 25.29 22.35 49.22 Example 2 22.55 19.57 50.85 Example 3 24.58 20.83 49.38 Comparative Example 1 19.78 14.89 33.33 Comparative Example 2 23.0 21.0 48.2 Comparative Example 3 15.44 12.83 30.22 Table 3 shows the limiting oxygen index LOI and residual carbon rate of the embodiments and comparative examples. As can be seen from the table, due to the additional addition of flame retardants, the limiting oxygen index of comparative example 3 can reach 28.4%, and the residual carbon rate is 36.2%, while the limiting oxygen indexes of comparative examples 1 and 2 are only 18% and 19.1%, respectively. In addition, the limiting oxygen indexes of embodiments 1 to 3 are 23.6%, 22.8%, and 24.3%, respectively, which are all higher than comparative example 1, and the residual carbon rate of embodiments 1 to 3 is increased by 16.7 to 19% compared with comparative example 1. The reason for this phenomenon is that the embodiments contain polyphosphoric acid components, which not only improve the limiting oxygen index of the waterborne polyurethane wood-like material, but also cause the polyphosphoric acid and the waterborne polyurethane pyrolysis product polyol to cross-link into carbon when the waterborne polyurethane is pyrolyzed, so that more phosphorus-containing products remain in the condensed phase, so that the waterborne polyurethane wood-like material prepared by the present invention has certain flame retardant properties.

[0050] Table 3 Limiting oxygen index LOI and carbon residue rate of examples and comparative examples sample LOI (%) Residual carbon rate (%) Example 1 23.6 32.5 Example 2 22.8 30.8 Example 3 24.3 33.1 Comparative Example 1 18 14.1 Comparative Example 2 19.1 19.8 Comparative Example 3 28.4 36.2 Figure 1 Schematic diagram of water contact angle of Example 1. It can be seen from the figure that the contact angle of Example 1 reaches 96.75°. This phenomenon may be due to the fact that bamboo nanocellulose is filled in the water-based polyurethane and generates hydrogen bonds with the water-based polyurethane, which enhances the interaction between the two interfaces and makes the water-based polyurethane wood-like material have a certain hydrophobicity. Therefore, the water-based polyurethane wood-like material prepared by the present invention has a certain water resistance.

[0051] Figure 2 The scanning electron microscope image of Example 1 shows that the pores of the waterborne polyurethane are elliptical, with a diameter of 50 to 150 μm and are relatively evenly dispersed. This indicates that the waterborne polyurethane wood-like material of the present invention foams relatively evenly during the preparation process, and bamboo nanocellulose can be relatively evenly dispersed in the waterborne polyurethane, which is beneficial to improving the mechanical properties of the waterborne polyurethane wood-like material.

[0052] The above are only specific embodiments of the present invention, but the technical features of the present invention are not limited thereto. Any simple changes, equivalent replacements or modifications made based on the present invention to solve basically the same technical problems and achieve basically the same technical effects are all included in the protection scope of the present invention.

Claims

1. A water-based wood-like polyurethane and a preparation method thereof, characterized in that: The preparation method of the water-based wood-like polyurethane stock solution comprises the following steps: (1) Preparation of bamboo nanocellulose: S1: Put bamboo powder and acetic acid solution into a reaction tank; put the reaction tank of the mixed solution into an electric rotary pot, heat it at 120-180°C for 45-80min, take it out, cool it at 24-28°C for 4.5-8h, finally separate the prehydrolyzed bamboo powder from the prehydrolyzate with a Buchner funnel, dry it at 35-50°C, and obtain a prehydrolyzed bamboo powder sample; S2: FeCl3·6H2O, tetrabutylammonium acetate and polyphosphoric acid are placed in a three-necked flask and reacted in a water bath at 60-80°C for 1.5-4h to form a uniform solution A; then, the pre-hydrolyzed bamboo powder sample prepared in S1 is added, reacted at a speed of 200-350r / min for 5-8h, deionized water is added to dilute the above mixture, and centrifuged at a speed of 7500-9000r / min for 5-16min, and the above operation is repeated 2-3 times to obtain a bamboo nanocellulose suspension; (2) Preparation of water-based wood-like polyurethane stock solution: It is composed of two components A and B. Polyoxytetramethylene glycol, dihydroxyethyl dodecylamine, polysilane, dibutyltin dilaurate and water are placed in a container at 25-40°C and stirred to obtain component A. Component B is 4,4'-methylenebis(phenyl isocyanate) and the bamboo nanocellulose suspension obtained in step (1) and stirred for 25-45 minutes to obtain a uniform mixture.

2. The water-based wood-like polyurethane stock solution according to claim 1, characterized in that: The ratio of the bamboo powder (g) to the acetic acid solution (mL) in step (1) is 1:(8-15), and the concentration of the acetic acid solution is 1.5 mol / L.

3. The water-based wood-like polyurethane stock solution according to claim 1, characterized in that: The molar ratio of FeCl3·6H2O, polyphosphoric acid and tetrabutylammonium acetate in the solution of step (1) is (0.1-0.5):(1-5):

1.

4. The water-based wood-like polyurethane stock solution according to claim 1, characterized in that: The ratio of the hydrolyzed bamboo powder sample (g) to solution A (mL) in step (1) is 1:(5-12), and the volume ratio of solution A to deionized water is 1:(1.5-2).

5. The water-based wood-like polyurethane stock solution according to claim 1, characterized in that: The mass ratio of polyoxytetramethylene glycol, dihydroxyethyl dodecylamine, polysilane, dibutyltin dilaurate and water in phase A of step (2) is (45-80): (8-20): (0.3-1.0): 1: (0.2-0.8).

6. The water-based wood-like polyurethane stock solution according to claim 1, characterized in that: The mass ratio of 4,4'-methylenebis(phenyl isocyanate) to the bamboo nanocellulose suspension in the phase B of step (2) is 1:(0.01-0.05).

7. A method for preparing the water-based wood-like polyurethane material according to claim 6, characterized in that: After stirring group A and group B at a mass ratio of 1: (1-1.5) at a speed of 550-750 r / min for 30-75 seconds, the mixture is immediately introduced into a mold for foaming for 1-2 hours to obtain a waterborne polyurethane wood-like material at a foaming temperature of 20-28°C.